Multiparametric MRI of intracranial aneurysms treated with the Woven EndoBridge (WEB): a case of Faraday's cage?. (10th February 2018) - Nawka, Marie Teresa; Sedlacik, Jan; Frölich, Andreas; Bester, Maxim; Fiehler, Jens; Buhk, Jan-Hendrik
Abstract : Objective: To evaluate multiparametric MRI including non-contrast and contrast-enhanced morphological and angiographic techniques for intracranial aneurysms treated with the single-layer Woven EndoBridge (WEB) embolization system applying simultaneous digital subtraction angiography (DSA) as the reference of standard. Materials and methods: We retrospectively identified all patients with incidental and acute ruptured intracranial aneurysms treated with a WEB device (WEB SL and WEB SLS) between March 2014 and June 2016 in our neurovascular center with early (within 7 days) postinterventional multiparametric MRI as well as mid-term (5–8 months) follow-up MRI and DSA available. Occlusion rates were recorded both in DSA and MR angiography (MRA). In MRI, signal intensities within the WEB as well as in the occluded dome distal to the WEB, if present, were measured by region-of-interest (ROI) analysis. Results: Twenty-five patients fulfilled the inclusion criteria. Rates of complete/adequate occlusion at mid-term follow-up were 84% with both MRA and DSA. A strong signal loss within the WEB was observed in all MR sequences at initial and follow-up examinations. ROI analysis did not reveal significant differences in non-contrast (P=0.946) and contrast-enhanced imaging (P=0.377). A T1-hyperintense thrombus in the non-WEB-carrying dome was a frequent observation. Conclusions: Signal intensity measurements in multiparametric MRI suggest that neither contrast-enhanced MRA nor morphological sequences are capable of revealing reliable information on the WEB lumen, presumably due to radio frequency shielding. MRI is therefore not suitable for confirming complete thrombus formation within the WEB.